Soil pH is a Key Determinant of Soil Fungal Community Composition in the Ny-Ålesund Region, Svalbard (High Arctic) - Zhang, Tao; Wang, Neng-Fei; Liu, Hong-Yu; Zhang, Yu-Qin; Yu, Li-Yan (Frontiers in Microbiology, 2016)
This study assessed the fungal community composition and its relationships with properties of surface soils in the Ny-Ålesund Region (Svalbard, High Arctic). A total of thirteen soil samples were collected and soil fungal community was analyzed by 454 pyrosequencing with fungi-specific primers targeting the rDNA internal transcribed spacer (ITS) region. The following eight soil properties were analyzed: pH, organic carbon (C), organic nitrogen (N), ammonium nitrogen (NH4+-N), silicate silicon (SiO42--Si), nitrite nitrogen (NO2--N), phosphate phosphorus (PO43--P) and nitrate nitrogen (NO3--N). A total of 57,952 reads belonging to 541 operational taxonomic units (OTUs) were found. Of these OTUs, 343 belonged to Ascomycota, 100 to Basidiomycota, 31 to Chytridiomycota, 22 to Glomeromycota, 11 to Zygomycota, 10 to Rozellomycota, whereas 24 belonged to unknown fungi. The dominant orders were Helotiales, Verrucariales, Agaricales, Lecanorales, Chaetothyriales, Lecideales, and Capnodiales. The common genera (>8 soil samples) were Tetracladium, Mortierella, Fusarium, Cortinarius, and Atla. Distance-based redundancy analysis (db-rda) and analysis of similarities (ANOSIM) revealed that soil pH (p=0.001) was the most significant factor in determining the soil fungal community composition. Members of Verrucariales were found to predominate in soils of pH 8-9, whereas Sordariales predominated in soils of pH 7-8 and Coniochaetales predominated in soil samples of pH 6-7. The results suggest the presence and distribution of diverse soil fungal communities in the High Arctic, which can provide reliable data for studying the ecological responses of soil fungal communities to climate changes in the Arctic.